Pulmonary Kaposi's Sarcoma: Diagnostic Features and Natural History in Patients with Acquired Immuneodeficiency Syndrome - Willis Tsai; Charles K Chan; Frances Shepherd; Carol Sawka (Canadian Respiratory Journal)
OBJECTIVE: This retrospective descriptive study was undertaken to highlight the diagnostic features and natural history of pulmonary Kaposi's sarcoma (KS).